ADDRESSING THE NEEDS OF LAWYERS IN LEGAL ENGLISH: A COMPARATIVE STUDY IN FOUR EUROPEAN UNION COUNTRIES - SIEROCKA, Halina; CHOVANCOVÁ, Barbora; KORDIĆ, Ljubica (Comparative Legilinguistics, 2019)
The paper reports on a survey into the linguistic needs of law professionals in four European countries, with the aim of identifying their views on the importance and their use of foreign language skills as well as their preferences for ELP course content. The data, obtained from a questionnaire survey of 536 legal professionals from Poland, the Czech Republic, Croatia and Germany, show that while the respondents agree on many of the major points, there are also some differences conditioned by the respondents’ age and the specific tasks they perform in the legal profession. The article argues that these variables have to be taken into consideration in the LSP context because they determine some of the specific needs that need to be addressed in Legal English instruction. It is suggested that the findings about the lawyers’ self-perceived importance and preferred styles of learning are highly relevant for LSP practitioners, particularly when designing Legal English programmes and testing materials.